Aplikasi Metode Numerik Dalam Analisis Stabilitas Lereng Pada Proyek Konstruksi Jalan - Alexander Adnan Hans Duha (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Slope stability is a critical aspect of road construction projects, particularly in areas with hilly topography and complex soil conditions. Slope failure can lead to serious consequences, including disruption of road functionality, economic losses, and safety risks. This study aims to analyze slope stability in a road construction project using a numerical method based on the Finite Element Method. The analysis was carried out using the strength reduction method to determine the factor of safety and to identify deformation patterns and slope failure mechanisms. The data used include results of soil investigations, soil mechanical parameters, slope geometry, and groundwater conditions. The analysis results indicate that the unreinforced slope is in a critical condition, with a factor of safety below the recommended value. The application of reinforcement systems, particularly soil nailing combined with drainage systems, significantly increases the factor of safety and reduces slope deformation. This study concludes that numerical methods provide a more comprehensive and realistic approach to slope stability analysis and are highly recommended for the design and evaluation of slopes in road construction projects with complex geotechnical conditions.